Comparative Advantage of Keyhole Right Flank Laparotomy and Ventral Midline Celiotomy for Ovariohysterectomy in Bitches - Acharya, Mohan; Sah, Manoj Kumar; Singh, Dinesh Kumar; Singh, Subir; Dhakal, Santosh (International Journal of Applied Sciences and Biotechnology, 2016)
The objective was to compare the relative advantage of adopting two ovariohysterectomy techniques: keyhole right flank laparotomy or ventral midline celiotomy, for ovariohysterectomy in bitches. Clinically healthy non pregnant bitches (n = 20; 2 ± 0.5 year age; 25 ± 5 kg weight) were used for the study. Bitches were randomly divided into two groups: group A (n = 10) bitches were ovariohysterectomized adopting keyhole right flank laparotomy, whereas in group B (n = 10) bitches were ovariohysterectomized adopting ventral midline celiotomy. Time required for completion of surgery, and length of suturing materials required was recorded, blood hematology and fibrinogen levels were analyzed, and post-operative wound healing was monitored. Length of chromic cat gut No. 1-0 (Ethicon; P < 0.01), and vicryl No. 3-0 (Ethicon; P < 0.001) used was more in ventral midline celiotomy compared with keyhole right flank laparotomy; however, similar length of chromic cat gut No. 2-0 (Ethicon; P = 0.47) was used in both the surgical techniques. Longer time (P < 0.001) was required to complete surgical procedure following ventral midline celiotomy compared with keyhole right flank laparotomy. Blood packed cell volume (PCV), total white blood cells (WBC), neutrophils, monocytes, and fibrinogen levels were statistically similar between the two surgical techniques. Wound healing was better in keyhole right flank laparotomy compared with ventral midline celiotomy. Conclusion: Keyhole right flank laparotomy required less time for surgery, less suturing materials and better wound healing compared with ventral midline celiotomy for ovariohysterectomy in bitches. Int J Appl Sci Biotechnol, Vol 4(2): 198-202